Metagenomic analysis of enteric bacterial pathogens affecting the performance of dairy cows in smallholder productions systems - Habimana, V.; Bett, R.C.; Amimo, Joshua O.; Kibegwa, F.M.; Githae, Dedan; Jung’a, J.O. (Academic Journals, 2018)
There is little information about the diversity of bacterial pathogens present in the rumen and feces of healthy cow and the subsequent effects on the performance of the host animal. The objectives of the present study were to genetically characterize the enteric bacterial pathogens found in the rumen fluid and cow feces and to identify the resistant genes responsible for antimicrobial resistance in the detected pathogens. The cow feces and rumen fluid samples (6 rumen fluid and 42 feces) were collected from lactating dairy cows. Using next generation sequencing, the enteric bacterial pathogens detected were screened for antimicrobial resistance genes using ResFinder-2.1 database in the center of Abricate. The characterized enteric bacterial pathogens include Escherichia coli, Salmonella enterica, Streptococcus agalactiae, Streptococcus pyogenes, Campylobacter coli, and Campylobacter fetus among others. Those enteric bacterial pathogens were also drug resistant bacteria except Campylobacter coli. The Campylobacter fetus fetus was identified as the only multidrug resistant bacterial pathogen detected in the cow feces. However, the abundant resistant genes detected confer resistance to tetracycline (17 genes from 209 contigs), beta-lactam (21 genes from 67 contigs), streptomycin (6 genes from 153 contigs), and sulfamethoxazole (2 genes from 72 contigs). This is the first study to identify the diversity of enteric bacterial pathogens from the station based and smallholder dairy cows in Kenya and Tanzania, respectively.